Analisis Kelayakan Finasial Produksi Jamu Beras Kencur Skala Rumah Tangga - Moni, Kandida Juita; Mushollaeni, Wahyu; Tantalu, Lorine (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Financial feasibility analysis is carried out to determine the financial feasibility of a product produced by industry, both large-scale industry and household-scale production. This research aims to obtain a calculation of the financial feasibility analysis of the kencur rice herbal drink product produced by the community on a household business scale. Aspects of financial feasibility analysis calculated in this research include COGS, BEP, R/C Ratio, NPV, IRR and PP. The results of the financial feasibility analysis show that the kencur rice herbal drink product is feasible to produce on a household scale or on a small scale. This is based on: (a) Cost of Production (HPP) of IDR 3,426; (b) selling price is IDR 6,500/bottle; (c) unit BEP of 16,255 and price BEP of IDR 105,655,630; (d) NPV with a positive value of IDR 524,143,499; (e) IRR for positive NPV is 60,390 and negative NPV is -287,375 which shows a higher figure compared to the bank interest rate, namely 212%; (f) R/C ratio of 1.90; (g) Payback Period which is shorter than the life of the project, namely 5 months.